Barriers to the implementation of green construction: a case study in Bandung, Indonesia - Firdaus, Adrian; Setiawan, Theresita Herni; Reynaldy, Joshua Ivan (International Journal of Integrated Engineering, 2018)
The concept of green construction is considered new in Indonesia. Wulfram I. Ervianto introduced a model of green construction assessment in Indonesia, which is called Assessment Green Construction model in 2015. This assessment consists of seven aspects, sixteen factors, and 142 indicators. This study is focused on the assessment of a building construction phase in Bandung, Indonesia by using Assessment Green Construction model. The output of the assessment shows that the source and material cycle aspect earns the highest implementation percentage, while water conservation aspect earns the lowest. The identified barrier from the highest percentage of occurrence to the lowest are no client demand, cost of investment, awareness, and site condition. The client demand issue could be overcome by the establishment of pertinent policy, official assessment system, and incentives. Contractor should aware about the business benefit of the investment. Further socialisation about several aspect of green construction is required to enhance the awareness of contractor. The site condition barrier should be addressed in the development of the Assessment Green Construction model